MODEL PEMBELAJARAN EFEKTIF BAGI GURU PENGGERAK DI SMK WIDYA DHARMA TUREN - FITRIASIH, NUR; Maulaniam Sholah, Hanif (LPPI Universitas Al-Qolam Malang, 2023)
This study discusses the Implementation of the Independent Curriculum in Islamic Religious Education Subjects (Face-to-Face Case Study at SMK Widya Dharma Turen). The purpose of this study is to describe the Implementation of the Independent Curriculum in Islamic Religious Education Subjects (Face-to-Face Case Study at SMK Widya Dharma Turen) in class X TJKT 1 students. Over time, the education curriculum continues to change because the curriculum is dynamic following the times. The independent curriculum in Islamic religious education subjects is very important, as a guide for human life in running life, the education process is not only on the academic aspect, but also the formation of morals (character) based on the Al-Quran and Al. Hadith. In the learning process of Islamic religious education (face-to-face case study at SMK Widya Dharma Turen) using the Problem Based Learning (PBL) learning model where the learning process directly involves students in solving a problem. This learning method has the advantage of making each student more independent, active, creative, critical reasoning, and has a character in accordance with the profile of Pancasila students. Keywords: Implementation, Merdeka Curriculum, Islamic Religious Education, Face-to-Face Case Study, Problem Based Learning.